Usulan Peningkatan Kualitas Pelayanan Rawat Inap Puskesmas Balapulang dengan Metode Service Quality dan Model Kano - Alex Kisanjani; Marulan Andivas; Misrianto (Jurnal Surya Teknika, 2021)
Puskesmas as the front line of health services need serious attention in terms of services quality. Puskesmas should be the first referral place with quality services, so that it can overcome various health problems that occur in the community. This study aims to provide suggestions for improvement in order to enhance the quality of inpatient services at the Puskesmas Balapulang. This study uses the Servqual and Kano Methods. The result of the study indicate that there are 3 service quality attributes that get priority for improvement, namely a comfortable inpatient room, easy and fast patient service process, and doctor visit on time according to schedule. Meanwhile, proposed improvement is to carry out routine maintenance of all Puskesmas facilities, provide trash bins in all patient ward, provide large service procedure information board, and penalize doctors for arriving late.